Synthesis report: Civil-military relations in international operations. A Danish perspective - Finn Stepputat (Danish Institute for International Studies (DIIS), 2009)
This report synthesizes the studies undertaken as part of the Danish government's initiative to strengthen the concerted civil and military planning and action in connection with peace supporting operations, with emphasis on the Danish engagement in Iraq and Afghanistan. It looks at how coherence is sought across three different but interlinked dimensions: across the institutions of the Danish government; Danish harmonization with other international actors; and Danish (and international) alignment with local and national actors.
Keywords: 300; Friedenssicherung; Internationale Truppe; Katastrophenhilfe; Dänemark; Afghanistan; Irak